2019
DOI: 10.3389/fphys.2019.00405
|View full text |Cite
|
Sign up to set email alerts
|

Physiological, Anthropometric, and Motor Characteristics of Elite Chinese Youth Athletes From Six Different Sports

Abstract: Several talent selection programs in elite sport schools are based on motor diagnostics for the purpose of recommending or transferring promising talents to general groups of sports; game sports, combat sports or endurance sports, and to more concrete sports such as gymnastics, skiing, or tennis. However, the predictive value of such testing is unclear. This study evaluated the concurrent validity of physiological performance prerequisites, body dimensions, as well as specific motor performances. The sample co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 44 publications
0
21
0
4
Order By: Relevance
“…Body height in swimming is widely recognized as an important talent factor and performance characteristic [53]. In table tennis, a low body weight as well as a short lower leg length [24] might enhance primarily the players'agility which plays an important role in elite table tennis performance [54].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Body height in swimming is widely recognized as an important talent factor and performance characteristic [53]. In table tennis, a low body weight as well as a short lower leg length [24] might enhance primarily the players'agility which plays an important role in elite table tennis performance [54].…”
Section: Discussionmentioning
confidence: 99%
“…The superiority of swimmers over athletes from the individual game sports in VC was confirmed by Bloomfield et al [23] as they found better values for 11-12 years old swimmers in comparison to tennis players of the same age. Also Zhao et al [24] found VC values of M = 5,071 ml (SD = 863) in Chinese U15/U16 age group swimmers, which were significantly higher than in a group, comprising youth athletes from five different other sports. In contrast, in that study VC was systematically lower in table tennis athletes (M = 3,823 ml; SD = 423).…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Jenis kegiatan yang ada dalam kurikulum penjasorkes pada SMP Negeri 3 Padang meliputi kegiatan pokok dan kegiatan pilihan. Kegiatan pokok meliputi senam, olahraga permainan (bolabasket, bolavoli dan sepakbola) dan atletik (Paz et al, 2019;Simon et al, 2019;Zhao et al, 2019). Sedangkan kegiatan pilihan meliputi aktifitas ritmik, olahraga luar sekolah atau petualangan dan olahraga potensial yang berkembang di daerah (Brymer & Feletti, 2019;Eastabrook & Collins, 2019;Siedentop et al, 2019).…”
Section: Pendahuluanunclassified